Difficulties of Prenatal Genetic Counseling for a Subsequent Child in a Family With Multiple Genetic Variations - Huang, Ting-Xuan; Ma, Gwo-Chin; Chen, Ming; Li, Wen-Fang; Shaw, Steven W. (Frontiers in Genetics, 2021)
Many parents with a disabled child caused by a genetic condition appreciate the option of prenatal genetic diagnosis to understand the chance of recurrence in a future pregnancy. Genome-wide tests, such as chromosomal microarray analysis and whole-exome sequencing, have been increasingly used for prenatal diagnosis, but prenatal counseling can be challenging due to the complexity of genomic data. This situation is further complicated by incidental findings of additional genetic variations in subsequent pregnancies. Here, we report the prenatal identification of a baby with a MECP2 missense variant and 15q11.2 microduplication in a family that has had a child with developmental and epileptic encephalopathy caused by a de novo KCNQ2 variant. An extended segregation analysis including extended relatives, in addition to the parents, was carried out to provide further information for genetic counseling. This case illustrates the challenges of prenatal counseling and highlights the need to understand the clinical and ethical implications of genome-wide tests.